Assessing the Performance of Daily Intake of a Homotaurine, Carnosine, Forskolin, Vitamin B2, Vitamin B6, and Magnesium Based Food Supplement for the Maintenance of Visual Function in Patients with Primary Open Angle Glaucoma. (17th January 2020) - Rolle, Teresa; Dallorto, Laura; Rossatto, Stefania; Curto, Daniela; Nuzzi, Raffaele
Abstract : Background . Glaucoma is a multifactorial optic neuropathy, which causes a continuous loss of retinal ganglion cells. Given the neurodegenerative nature of glaucoma, the necessity for neuroprotective intervention still arises, to be added alongside hypotonic therapy. Objective . The objective of this study was to assess the effect of daily intake of a homotaurine, carnosine, forskolin, vitamins B1, B2, and B6, folic acid, and magnesium based supplement (GANGLIOLIFE®) on the progression rates of the visual field in patients with progressive POAG despite good tonometric compensation and to assess the most suitable dosage. Methods . This is a monocentric nonrandomized experimental clinical study. Patients with mean deviation (MD) ranging from −2 dB to −15 dB with MD progression ≥1 dB in the previous year and IOP values of ≤18 mm Hg were included. All the patients underwent supplement therapy for a period of 6 months. For the first 2 months, they took 2 tablets a day, and for the following 4 months, 1 tablet a day. The patients were assessed before the start of treatment, time 0 ( T 0 ), after 2 months ( T 1 ), and after 6 months ( T 2 ) of therapy. At each check-up, patients were given a full eye test including perimetry, RNFL, and GCC using FD-OCT, PERG, contrast sensitivity, and QoL evaluation using the Glaucoma Symptom Scale questionnaire and National Eye Institute Visual Function Questionnaire 25. Results . 31 patients with a mean age of 70.80 ± 8.77 were included. At T 1 and T 2, the mean values of MD were lessened (MD = −5.37 ± −2.91, P < 0.01, and MD = −5.48 ± 3.15, P < 0.05, respectively) compared to T 0 (MD = -5.98 ± 2.83). Patients also demonstrated a significant reduction in IOP (P < 0.01 ), improved light sensitivity (P < 0.01 ) and contrast sensitivity (P < 0.05 ), and a better quality of life (P < 0.05 ). Conclusions . Treatment with a supplement which includes homotaurine, carnosine, forskolin, vitamins B1, B2, and B6, folic acid, and magnesium has been shown to be able to slow down the rate of progression of functional damage and improve visual function after 2 and 6 months of daily intake. Quality of life showed significant improvement.